Great Canadian Lagerstätten 6. Mistaken Point Ecological Reserve, Southeast Newfoundland - Liu, Alexander; Matthews, Jack (Geoscience Canada, 2017)
Mistaken Point Ecological Reserve (MPER) World Heritage Site, on the southeastern coast of Newfoundland, Canada, is one of the foremost global Ediacaran fossil localities. MPER contains some of the oldest known assemblages of the softbodied Ediacaran macrobiota, and its fossils have contributed significantly to Ediacaran paleobiological research since their initial discovery in 1967. Preservation of multiple in situ benthic paleocommunities, some comprising thousands of specimens, has enabled research into Ediacaran paleoecology, ontogeny, taphonomy, taxonomy and morphology, offering insights into the possible phylogenetic positions of Ediacaran taxa within the tree of life. Meanwhile, a thick and continuous geological record enables the fossils to be placed within a wellresolved temporal and paleoenvironmental context spanning an interval of at least 10 million years. This article reviews the history of paleontological research at MPER, and highlights key discoveries that have shaped global thinking on the Ediacaran macrobiota.